AUDIT BERBASIS RISIKO DALAM PENGUJIAN ATAS PENGENDALIAN INTERN PADA SIKLUS PENDAPATAN - Megasari, Ita (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of the research is to find out how the implementation of Audit Berbasis Risiko (ABR) in examining internal control especially in the revenue cycle. This research is a qualitative research that uses case study approach. This research focuses on the implementation of ABR at Faculty of Psychology â University of Surabaya, exactly âPusat Konsultasi dan Layanan Psikologi (PKLP)â. The revenue of activity consists of the stages of acceptance of the order, the credit approval stage, the stage of billing, receipts, and invoices, shipment and delivery stages of psychological test result report, collection, cash receipts.The result of this research shows that internal auditor should prioritize testing and observation in an activity that has a significant risk. This risk can appear from external and internal factors. In this research is found 10 (ten) risks appear on revenue cycle â PKLP, and risks that affect most of the risk is transactional risk. The critical problem area of research is the stages of acceptance of the order, collection, and , cash receipts. Thereore, it is necessary to further improvement and monitoring of the improvement activities for both the CPA.Keywords: risk-based audit, critical problem areas, risk management